Analysis on Reform of the Relationship between Teaching and Learning of College English Teaching - Yuexia Cui (SHS Web of Conferences, 2014)
There are substantial changes of the relationship between teaching and learning in college English teaching. On one hand, the dominant role of teachers has been changed. New teaching idea advocates the dominant role of students and also their active participation in teaching. On the other hand, the reform has combined teaching with learning which propels the interaction between them. Thus, based on the features of college English teaching, this paper, which aims to promote the quality of college English teaching and help cultivate professional and high-quality inter-disciplinary talents for our society, has analyzed the relationship between teaching and learning and came up with solutions to problems lurking in present college English teaching after specific reflection.